Pengaruh Kompetensi Kerja Dan Kedisplinan Waktu Terhadap Kinerja Pegawai Pada Dinas Pekerjaan Umum Dan Tata Ruang Kabupaten Nias - Idam Murniati Zega; Delipiter Lase; Odaligoziduhu Halawa; Heseziduhu Lase (Visi Sosial Humaniora, 2024)
This research was conducted at the Public Works and Spatial Planning Office of Nias Regency. The researcher found that: 1) the staff needs do not meet the job competency standards; 2) academic backgrounds are not relevant to roles or job functions; 3) the implementation of main duties and functions is not optimal; and 4) there are delays in staff attendance and departure times. The objectives of this research are to explain the effect of work competence on employee performance at the Public Works and Spatial Planning Office of Nias Regency, to explain the effect of time discipline on employee performance at the same office, and to investigate the synergistic relationship between work competence and time discipline in the context of improving employee performance. Data collection techniques included observation and the distribution of questionnaires to 52 employees at the Public Works and Spatial Planning Office of Nias Regency. Based on the coefficient of determination (R Squared) test, work competence (X1) and time discipline (X2) account for 44.3% of the effect on the dependent variable (Y). The remaining influence is due to other factors not discussed in the study. The F-test value is 19.458, which is greater than the F-table value of 3.19, indicating that the regression model as a whole has a significant effect on the dependent variable. The model is considered fit since the significance value (Sig) is less than 0.05, with a significant value of 0.000, which is less than 0.05. It can be concluded that the independent variables have a significant simultaneous (combined) effect on the dependent variable and that there is a synergistic relationship between work competence (X1), time discipline (X2), and employee performance (Y) at the Public Works and Spatial Planning Office of Nias Regency. Keywords: Job Competence, Time Discipline, and Employee Performance.